2016
DOI: 10.1111/nzg.12143
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and the embodied practices of Bhutanese‐New Zealander teenage women: Young bodies, going out and sexual practices

Abstract: This paper examines the ways in which the lived experiences and the embodied practices of Bhutanese teenage women refugees are entangled with notions of ‘homeliness’, ‘being in place’ and discourses around mobility. For these women, constraints associated with cultural values can create a somewhat paradoxical ‘unhomeliness’ and feelings of ‘being out of place.’ The experience of being a refugee can heighten the importance of home as a refuge, and the desire to build a new home in a wider community. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Participant 1 believed that her family thought she was selfish and a "bad person", despite this not being the case, which resulted in her feeling as if her family did not really know who she is (Basnet, 2016). Therefore, Participant 1 demonstrated how differences can exist between how their self-perceptions and how their families perceived them (Bergquist et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Participant 1 believed that her family thought she was selfish and a "bad person", despite this not being the case, which resulted in her feeling as if her family did not really know who she is (Basnet, 2016). Therefore, Participant 1 demonstrated how differences can exist between how their self-perceptions and how their families perceived them (Bergquist et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may also be related to gender roles, as girls are often expected by their parents to help out more in the home and to care for younger siblings (Dabbagh et al, 2017;Frounfelker et al, 2017). Previous studies have found that the gender of refugees is associated with different lived experiences (Basnet, 2016;Cajax & Berman, 2010;Hatoss & Huijser, 2010;Koh et al, 2013), as youth may be socialized along traditional gender lines (Deng & Marlowe, 2013). Traditional gender roles reinforce the idea that women belong in the house taking care of children, whereas men should engage in paid labour outside of the home (Hatoss & Huijser, 2010;Kim et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, parents are more likely to monitor the activities and behaviours of refugee girls as opposed to boys (Basnet, 2016;Caxaj & Berman, 2010;Koh et al, 2013), which Participant 1 discussed in relation to her mother being at home more often in Canada due to a lack of employment, which gave her extra time to watch over her. These gendered expectations have implications for engagement in extra-curricular activities, parental monitoring, postsecondary education, hanging out with friends, and developing relationships (Basnet, 2016;Hatoss & Huijser, 2010;Koh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%